Daughters and Granddaughters of Farmworkers: Emerging from the Long Shadow of Farm Labor - Barbara Wells (Rutgers University Press, 2013)
As an Anglo graduate student in sociology, I was honored and privileged to work with a leading Latina family sociologist, Maxine Baca Zinn. I learned from her that to be a successful scholar, one must ask the right questions and be committed to the virtue of hard work. In working with Maxine, I became convinced of the explanatory power of a structural analysis that takes into account the intersection of race, social class, and gender. The honor continued as we collaborated on what is by now a well-known analysis of Latino families, â€œDiversity within Latino Families: New Lessons for Family Social Scienceâ€ (2000). Beyond specific Latina/o concerns, I have been privileged to work with Maxine and D. Stanley Eitzen on a diversity-based approach to family sociology in the textbook, Diversity in Families. It is the convergence of these two themes in my intellectual developmentâ€”seeing the analytical promise of structural analysis and developing an interest in Latino familiesâ€”that brought me to the present project. My decision to undertake this research project was further encouraged by what I perceived to be a challenge put forward by authors of an article in a leading journal in the field of family studies, the Journal of Marriage and Family. In a review of the research on ethnic families from the 1990s, â€œMarital Processes and Parental Socialization in Families of Color: A Decade Review of Researchâ€ (2000), McLoyd and her coauthors concluded that if one had to deduce the current demographic realities of the United States from the quantity of research on Latino families, one would conclude that these families were a â€œminisculeâ€ percentage of the population. The authors called for more and better research on Latino families. The circumstances have changed in ensuing years as more research has centered on Latino families. Much of the new research is excellent, but it has been clear that more qualitative research is needed. This book is the product of a process of thinking carefully about how I might contribute to the body of research on this important segment of the U.S. population.